(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article discusses modern technologies for producing C₉ mononuclear arenes from hydrocarbon pyrolysis products. A process scheme for extracting aromatic compounds from pyrolysis gasoline is presented, including hydrotreating, selective extraction, and fractional distillation. Special attention is given to methods for obtaining trimethylbenzenes and propylbenzenes as key representatives of the C₉ fraction. Their industrial applications in petrochemical synthesis, solvents, and polymer production are also described. Additionally, recent advances in process optimization and environmental considerations are highlighted.